Aransemen Lagu pada Buku Ende No. 212 Haholongan Na Badia dalam Kuartet Saxophone pada Ibadah Minggu di HKBP Pardomuan Silangkitang Tapanuli Utara - Jeverwandi Sitohang; Boho Parulian Pardede; Testi Bazarni Zebua; Monang Asi Sianturi; Roy JM. Hutagalung (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
The purpose of this study is to develop the song "Haholongan Na Badia" in the Saxophone Quartet. The motif in this song still uses the original melody of the song but there is a slight change in tempo and. It aims to be more wise and pleasant to listen to and adjust to the conditions of worship. This study uses qualitative research, namely by describing the Song Arrangement in the Ende Book No. 212 "Haholongan Na Badia" in the Saxophone Quartet at Sunday Worship at HKBP Pardomuan This research was carried out in July - August 2024. By observing, literature and with several sources related to saxophone instruments and the HKBP Pardomuan Church in writing and unwritten. The result of this research is that the Song in the Ende Book No.212 "Haholongan Na Badia" is a very wise song and has a meaning and message in its verses This form of arrangement is a new concept and presentation of the song Tu Jolom O Debatang Ku in the form of a saxophone quartet arrangement. This thesis discusses the presentation, arrangement process of the Saxophone Quartet in the song of the book Ende No. 212 "Haholongan na badia" in accompanying Sunday worship at HKBP Pardomuan. For the rhythm sign, the author uses the 3/4 rhythm which is in the original score of the 4/4 song and the basic note Bb = do and with the tempo of Adagio MM 70.